Biodiesel production from waste cooking oil using heterogeneous CaO/Zn catalyst: yield and reusability performance - Ali, Nur Afiqah; Khairuddin, Nozieana (Faculty of Science, Chiangmai University, 2023)
Biodiesel is a renewable, biodegradable, and non-toxic fuel derived from vegetable oils, animal fats, or recycled cooking oils. Biodiesel can be used as a direct replacement for diesel in diesel engines with minimal or no modification, and it has several advantages over conventional diesel. Eggshells, on the other hand, are composed mainly of calcium carbonate (CaCO3), a valuable resource for various industrial and agricultural applications. Improper disposal of eggshells can cause environmental pollution and discarding of eggshells in landfills takes up valuable space and emits potent greenhouse gases such as methane. The current study focuses on biodiesel production from waste cooking oil (WCO) using heterogeneous catalysts from eggshells impregnated with Zinc (Zn) metal. The transesterification process can produce biodiesel using WCO in the presence of a catalyst. The free fatty acid (FFA) of WCO is 0.45 mg KOH/g lower, enabling the transesterification process. The CaCO3 present in the eggshell will be converted into calcium oxide (CaO) after calcination. SEM analysis showed the catalysts morphology (CaO and CaO/Zn) changes after undergoing calcination and zinc impregnation processes. In this study, eggshells were utilized as a potential solid catalyst for biodiesel synthesis through transesterification. The reusability of the catalyst was also investigated. The reused catalyst produced an average yield of 65%.